Pelatihan Operasi, Perawatan dan Serah Terima Mesin Pencacah Rumput untuk Kelompok Tani Hutan Pasirsela : Pengabdian - Dibyo Setiawan; Haryadi; Budi Triyono; Apri Setiawan; Iqbal Hidayatullah; Thomas Aquinas J S; Khairullah Ijlal; Bunga Muthia Dien; Syarah Widia Islamiati R (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Lebakaso Hamlet, Cikahuripan Village, Cimanggung District, Sumedang Regency, is a hamlet that requires attention in increasing livestock management capacity. The community already has a village organization, the Pasir Sela Forest Farmers Group (KTH), to improve livestock management. A green fodder chopper machine and machine maintenance operation training are needed. The purpose of the Community Service program contract activity is to improve the quality of partners and provide training, implementation methods for problem identification activities, preparing machine designs, machine procurement and manufacture, providing machine operation and maintenance training, and machine handover and activity reporting. The results of the activity have been realized according to plan based on the implementation method of the availability of a chopper machine that has an electric motor drive, is capable of chopping stems and grass, has a filter feature, and speed variations with a choice of pulley sizes and machine construction that can be easily mobilized. The implementation of operation and maintenance training and handover of the chopper machine tool was successfully carried out with PkM KTH Pasir Sela partners. Furthermore, to ensure the allocation of the machine and its utilization, monitoring and evaluation are carried out.